(untitled) (KULT_online, 2010)
In 59 articles, Handbuch Biographie (Biography Handbook) captures the wide variety of the biographical praxis in different media from sociological, philological, and cultural perspectives. The handbook regards ’biography’ as a ’cultural universal’ (cf. p. XII) which is an important part of our society, as can be seen in bookstores, on television, and on the Web. Despite the unavoidable ’rough edges’ inherent to any project of such wide scope, the Handbuch Biographie marks a roundly successful approach to the genre.